A prospective study of outcome in patients with intra-abdominal hypertension - Rampal, Kapil; Prajapati, Devendra K.; Sharma, Meghna; Singh, Parampreet; Singh, Jasmaan; Singh, Harinder (International Surgery Journal, 2021)
Background: Intra-abdominal hypertension (IAH) and Abdominal compartment syndrome (ACS) is increasingly recognized in critically ill patients, and the deleterious effects of increased intra-abdominal pressure (IAP) are well documented. It is known to affect almost all the system in the body, but mainly the renal, cardiovascular and pulmonary systems. The purpose of this study is to prospectively observe the outcome of IHP in patients admitted in ICU, acute surgical and emergency wards over three years and give our recommendations based on the outcome in such patients. Methods: We measured intravesical pressure using simple manometry to measure IAP. Results: We observed cardiac dysfunction in 16.30%, renal dysfunction in 10.86%, respiratory dysfunction in 21.74% and mortality of 15.2%. Significant mortality was associated with IAH grade II (55.6%) and grade III (100%). Conclusions: Due to the contribution towards mortality and common occurrence we suggest that intra-abdominal pressure be measured in ICU conditions.